Synthesis and Epoxidation of Flav-3-enes as Methodology for the Biomimetic Preparation of Flavan-3,4-diols - van Jaarsveldt, Jeanette; Marais, Charlene; van Tonder, Johannes H.; Bezuidenhoudt, Barend C. B. (Synthesis, 2023)
Since flavonoids exhibit a remarkable number of pharmacological properties like antioxidant, anti-inflammatory, and antimicrobial activities, a great deal of work has been done on the medicinal and therapeutical application of these compounds. Despite the central role of flavan-3,4-diols in the synthesis of many other classes of flavonoids, only a few methods for the preparation of these compounds have been reported. In this paper, the results on the preparation of methoxy-substituted flavan-3,4-diols, displaying natural substitution patterns, from readily available starting materials through a 3-step process is disclosed. It is also indicated that the 4-aryl-substituted analogues can become available from the corresponding flav-3-enes if an aromatic nucleophile is added during the dimethyldioxirane (DMDO) epoxidation process.
Keywords: aldol condensation; reductive cyclization; epoxidation; dimethyldioxirane; flav-3-ene; flavan-3,4-diol